The integration of nanoscale imaging and quantitation of nanomechanical properties in microbiology - Geertje Van Keulen (Microbiology Today, 2016)
Recent developments in nanotechnology enable the imaging, quantification and manipulation of materials at the near-atomic level. The number of applications of atomic force microscopy (AFM) in the life sciences is increasing, now allowing the integrated study of topological and quantitative nanoscale mechanical characterization of living cells and their interactions with their environments, which was inconceivable until recently.